Oxyallyl cation promoted dearomative semipinacol rearrangement: a facile stereodivergent synthesis of spiro-indolines with contiguous quaternary centers. Issue 54 (14th June 2021) - Xie, Yu-Yang; Wang, Yun-Peng; Zhao, Xiao-Jing; Wang, Ai-Fang; Chen, Zhi-Min; Tu, Yong-Qiang
Abstract : A novel oxyallyl cation promoted semipinacol rearrangement of indole-type allylic alcohols was disclosed for the stereo-divergent synthesis of spiro-indolines. Abstract : A novel oxyallyl cation promoted semipinacol rearrangement of indole-type allylic alcohols was disclosed for the stereodivergent synthesis of spiro-indolines. A variety of spiro-indolines were obtained with moderate to good yields. Three contiguous stereocenters, two of which are vicinal quaternary centers, were effectively formed with good diastereoselectivity. It is worth noting that two diastereoisomers of rearranged products can be readily achieved by easily regulating the reaction conditions. This method may provide an applicable approach for the synthesis of natural indole alkaloids.